Design of a safety operational envelope protection system for the pitch angle of a submarine. (May 2017) - Park, Jong-Yong; Kim, Nakwan
Submarines have a safety operating envelope, the boundary of which is closely related to structural limits and the safety of crew. An envelope protection system guarantees that the submarine does not exceed the boundary, which reduces the frequency of operational accidents and mission time. In this article, an envelope protection system for the pitch angle is designed for a submarine. The envelope protection system consists of limit detection and limit avoidance. Limit detection is designed using a dynamic trim algorithm, and command limiting is used for the limit avoidance. An artificial neural network is adopted for on-line learning and modeling uncertainty compensation, and a linear quadratic regulator is employed to stabilize the error dynamics. A submarine maneuvering simulation program developed from the experimental data is used to validate the designed envelope protection system. The simulation results show the effectiveness of the envelope protection system.